RESULTS OF PARALLELISATION OF EXISTING ELECTROMAGNETIC FINITE ELEMENT CODES ON SOME DIFFERENT PARALLEL ARCHITECTURES - Dracopoulos, M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper the results obtained from the parallelisation of some 3D industrial electromagnetic Finite Element codes within the ESPRIT Europort 2 project PARTEL are presented. The basic guidelines for the parallelisation procedure, based on the Bulk Synchronous Parallel approach, are presented and the encouraging results obtained in terms of speed-up on some selected test cases of practical design significance are outlined and discussed. [Vol. 12, No. 2 (1997), Special Issue on Numerical Field Calculations in Electrical Engineering, pp 107-112]